Foreign Direct Investment, Source Country Heterogeneity and Management Practices - Fredrik Heyman; Pehr-Johan Norbäck; Rickard Hammarberg (Research Institute of Industrial Economics (IFN), 2014)
This paper examines whether and, if so, why source country heterogeneity exists in foreign direct investment (FDI). Using detailed data on all Swedish firms for the period from 1996 to 2009, we find statistical evidence that affiliate performance differs systematically across source countries. For instance, affiliates of US multinational enterprises (MNEs) are, on average, approximately three times more productive than affiliates headquartered in the Nordic countries. One possible explanation for these discrepancies is differences in organization practices across source countries. Using new firm-level data from the World Management Survey to estimate a global index of the quality of management practices for MNEs with headquarters in our source countries of interest, we find that source country heterogeneity in affiliate performance is highly correlated with differences in management practices.
Keywords: F21; F23; L10; M10; 330; Multinational firms; FDI; Management practices; Firm performance